2007
DOI: 10.1007/s11483-007-9031-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Active Compounds on Iron Catalyzed Oxidation of Methyl Linolenate in AOT–Water–Hexadecane Systems

Abstract: Edible oils contain minor surface active components that form micro-heterogeneous environments, such as reverse micelles, which can alter the rate and direction of chemical reactions. However, little is known about the role of these micro-heterogeneous environments on lipid oxidation of bulk oil. Our objective was to evaluate the ability of water, cumene hydroperoxide, oleic acid, and phosphatidylcholine to influence the structure of reverse micelles in a model oil system: sodium bis(2-ethylhexyl) sulfosuccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Chayasit reported similar results of this study in that iron (II) sulfate increased the oxidation rate of methyl linoleate in the sodium bis(2-ethylhexyl)sulphosuccinate (AOT) reverse micelle system, but did not change the oxidation rates without AOT reverse micelles (Chayasit et al, 2007). Both iron (II) sulfate and iron (III) sulfate are water-soluble and could partitioned into the water core of association colloids as iron (II) and iron (III) ions.…”
Section: Impact Of Types Of Iron On the Oxidative Stability Of Ethyl supporting
confidence: 80%
See 1 more Smart Citation
“…Chayasit reported similar results of this study in that iron (II) sulfate increased the oxidation rate of methyl linoleate in the sodium bis(2-ethylhexyl)sulphosuccinate (AOT) reverse micelle system, but did not change the oxidation rates without AOT reverse micelles (Chayasit et al, 2007). Both iron (II) sulfate and iron (III) sulfate are water-soluble and could partitioned into the water core of association colloids as iron (II) and iron (III) ions.…”
Section: Impact Of Types Of Iron On the Oxidative Stability Of Ethyl supporting
confidence: 80%
“…Iron is one of the most important prooxidative transition metals found in oils due to its high concentration. Water-soluble iron compounds, such as iron (II) sulfate and iron (II) chloride, were reported to be prooxidative in oils with association colloids (Chayasit, Stanley, Strey, McClements, & Decker, 2007;Chen, Panya, McClements, & Decker, 2012). However, the effect of oil-soluble and oil/water insoluble iron compounds has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of hydroperoxides to reduce interfacial tension and thus be amphiphilic was also confirmed by Nuchi et al Trunova et al reported that both cationic reverse micelles formed by cetyltrimethylammonium bromide (CTAB) and anionic reverse micelles formed by sodium dodecyl sulfate (SDS) increased the decomposition of ethylbenzene and limonene hydroperoxides . In another reverse micelle system that used AOT as surfactant (AOT/water/hexadecane), the authors found that lipid oxidation rates of methyl linolenate were altered upon the addition of cumene hydroperoxides, water, oleic acid or PC …”
Section: Phospholipids In Lipid Oxidationmentioning
confidence: 80%
“…70 In another reverse micelle system that used AOT as surfactant (AOT/water/hexadecane), the authors found that lipid oxidation rates of methyl linolenate were altered upon the addition of cumene hydroperoxides, water, oleic acid or PC. 77 The presence of phospholipid reverse micelles in bulk oils creates oil-water interfaces where hydrophilic (e.g. iron) and amphiphilic (e.g.…”
Section: Prooxidant Properties Of Phospholipidsmentioning
confidence: 99%
“…Major factors for lipid oxidation are the degree of unsaturation in lipids and the presence of oxygen molecules such as triplet or singlet oxygen. Also, minor components in oils including transition metals, moisture, phospholipids (PL), sterols, and the presence of antioxidants greatly influence oxidative stability [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%